SURVIVAL RATE of TIGER GROUPER LARVA (Epinephelus fucoguttatus) HOUSEHOLD SCALE ON THE NORTH COAST of BALI - I Komang Yudha Wirawan; Liga Insani; Muh. Sulaiman Dadiono (Journal of Fish Health, 2021)
Tiger grouper (Epinephelus fuscoguttatus) hatchery at the household scale has contributed to the increase in national grouper seed production. The main problem in tiger grouper cultivation is the availability of superior seeds. Where superior tiger grouper seeds must have fast growth, be resistant to new environments, low FCR, have perfect morphology and be resistant to. Superior seeds of tiger grouper can be seen from the value of Survival Rate (SR), where superior seeds will have a much higher SR when maintained. The purpose of this study was to determine the Survival Rate of tiger grouper hatchery in household-scale hatcheries located on the North Coast of Bali as the main parameter and water quality as a supporting parameter. Methods of data collection is done by using 4 ways: survey, active participation, observation, and interviews. Survival rate data analysis was carried out by performing calculations based on the SR calculation formula and analyzed descriptively. The results of observations of water quality are classified as good for the value of Salinity (33-35 ppt), Temperature (28-29.4 oC), and DO (6-6.5 ppm). While the pH value can be said to be not good for tiger grouper hatchery and rearing with a pH value of (7.3-7.4). The result of the calculation of the Survival Rate is 20% with a total of ± 24,000 seeds. From the percentage of survival rate, it can be said that the survival rate of tiger grouper larvae in this household-scale hatchery is still low. However, it should be noted that a low survival rate in grouper hatcheries does not always affect the value of profits and losses of a grouper hatchery business.